Altered gut microbiota and inflammatory markers in depression: A cross-sectional study. - Pati, Saswati Sucharita; Biswal, Sudhansu Priyadarshini; Sahoo, Duryodhan; Mahanta, Jharana (Student's Journal of Health Research Africa, 2025)
Background: Depression is a multifactorial mental health disorder influenced by psychological, biological, and environmental factors. Emerging evidence highlights the role of the gut–brain axis, particularly gut microbiota and inflammatory responses, in the pathophysiology of depression. Aim: To investigate alterations in gut microbiota composition and their association with systemic inflammatory markers in individuals diagnosed with depression. Methods: A cross-sectional observational study was conducted over one year, involving 100 participants 50 with clinically diagnosed depression and 50 healthy controls. Stool and blood samples were collected to analyze gut microbiota via 16S rRNA sequencing and inflammatory markers (CRP, IL-6, TNF-α) via ELISA. Data were analyzed using SPSS version 23.0. Results: Participant characteristics included religion and educational status, with 68% of participants identifying as Hindu, 22% as Muslim, and 10% as others; 54% had completed secondary education, while 46% had higher education. Depressed individuals showed significantly elevated levels of CRP (6.2 ± 2.1 mg/L), IL-6 (11.4 ± 3.8 pg/mL), and TNF-α (19.7 ± 6.5 pg/mL) compared to controls (p < 0.001). Gut microbiota analysis revealed a reduction in beneficial bacteria (Lactobacillus and Bifidobacterium) and an increase in Proteobacteria and Firmicutes/Bacteroidetes ratio in the depression group. Significant negative correlations were observed between beneficial bacteria and inflammatory markers (Lactobacillus vs. CRP (r = –0.52, p < 0.001) and Bifidobacterium vs. TNF-α (r = –0.44, p = 0.004)), indicating a potential link between microbial dysbiosis and systemic inflammation in depression. Conclusion: The findings suggest that depression is associated with gut microbiota imbalance and elevated inflammatory markers. Dysbiosis may contribute to systemic inflammation reinforcing the role of the gut–brain–immune axis in depression's pathogenesis. Recommendations: Future longitudinal studies should explore microbiome-based therapeutic interventions, such as probiotics or dietary modulation, as adjunctive treatments for depression. Incorporating gut health screening in mental health assessments may enhance holistic management.